A Complex Case of Cholestasis in a Patient with ABCB4 and ABCB11 Mutations - Cardoso, M (2019)
The low-phospholipid-associated cholelithiasis (LPAC) syndrome is a form of symptomatic cholelithiasis occurring in young adults, characterized by recurrence of symptoms after cholecystectomy and presence of hepatolithiasis. The case refers to a healthy 39-year-old Caucasian male who presented with abdominal pain and jaundice. His blood tests showed conjugated hyperbilirubinemia and elevated liver enzymes (total bilirubin 6.65 mg/dL, γ-glutamyltransferase 699 IU/L) and abdominal computed tomography revealed dilation of common bile duct and left intrahepatic ducts. Magnetic resonance cholangiopancreatography identified choledocholithiasis, retrieved by endoscopic retrograde cholangiopancreatography, after which there was a worsening of jaundice (total bilirubin 23 mg/dL), which persisted for several weeks, possibly due to ciprofloxacin toxicity. After an extensive workup including liver biopsy, the identification of two foci of hepatolithiasis on reevaluation abdominal ultrasound raised the hypothesis of LPAC syndrome and the patient was started on ursodeoxycholic acid, with remarkable improvement. Genetic testing identified the mutation c.1954A>G (p.Arg652Gly) in ABCB4 gene (homozygous) and c.1331T>C (p.Val444Ala) in ABCB11 gene (heterozygous). In conclusion, we describe the unique case of an adult male with choledocholithiasis, hepatolithiasis, and persistent conjugated hyperbilirubinemia after retrieval of stones, fulfilling the criteria for LPAC syndrome and with possible superimposed drug-induced liver injury, in whom ABCB4 and ABCB11 mutations were found, both of which had not been previously described in association with LPAC.